In-situ toughened heat-resistant polylactic acid composition, product thereof, and preparation method and application of product
By introducing modified polybutylene succinate and nucleating agent into polylactic acid, an in-situ toughening and heat-resistant polylactic acid composition is formed, which solves the problem of insufficient brittleness and heat resistance of polylactic acid materials, and achieves higher impact and heat resistance.
Patent Information
- Application Number
- CN202411906799.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-21
AI Technical Summary
Polylactic acid biodegradable materials have high hardness and high brittleness and poor heat resistance, which limits their application in disposable straws, lunch boxes, films, and injection molded products that have high requirements for impact and heat resistance.
Modified polybutylene succinate is prepared by reacting polybutylene succinate with a functional modifier or chain extender in the presence of an initiator and melt blended with polylactic acid and nucleating agent to form an in situ toughening and heat-resistant polylactic acid composition.
The impact resistance and heat resistance of polylactic acid are significantly improved, their compatibility with polybutylene succinate is enhanced, the reaction steps are simplified, and the thermodynamic stability of the product is improved.
Smart Images

Figure CN119662002A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and specifically relates to an in-situ toughened heat-resistant polylactic acid composition, a product thereof, and a preparation method and use of the product. Background Art
[0002] Polylactic acid (PLA) is a bio-based thermoplastic polymer material with good biocompatibility and biodegradability. It exhibits hard and brittle properties, which meets the carbon reduction requirements of environmentally friendly materials. However, its insufficient toughness and slow crystallization rate limit its application in disposable straws, lunch boxes, films, and injection molded products with high requirements for impact resistance and heat resistance. In order to improve the impact strength and heat resistance of PLA, a variety of strategies have been adopted, including copolymerization, plasticization, addition of rigid fillers, and blending with different flexible polymers or rubbers.
[0003] Polybutylene succinate (PBS) is commonly used as a flexible segment for toughening modification of PLA. However, the toughening effect is not ideal simply by physically blending the two, and the heat deformation temperature is low, and there is an obvious island phase separation morphology. In order to enhance the toughening effect of PBS on PLA, studies have shown that the physical properties of the blending system of PLA and PBS can be optimized through modification methods such as elastomer compounding, volume expansion and chain extension.
[0004] The thermodynamic compatibility between PLA and PBS is extremely poor, so compatibilizers are usually added to enhance the compatibility of PLA and PBS. For example, patent CN 115785632 A proposes a method for improving the compatibility of PLA / modified PBS, by using acetate to promote the transesterification reaction between PLA and PBS during the melt extrusion process, and the resulting copolyester can significantly enhance the toughness as a compatibilizer, but it will also affect the thermal stability of the blended material, and the process of the transesterification reaction is difficult to control. Patent CN115558070 A uses a ternary mixture of PLA polyol, PBS polyol and isocyanate, and performs a screw extrusion reaction under the action of a catalyst to prepare a high molecular weight resin with a body branched structure as a compatibilizer. However, it is easy to form a cross-linked structure when preparing the terpolymer, which has an adverse effect on the extrusion processing of the PLA / PBS blend.
[0005] CN 115975358 A discloses a polylactic acid-based biodegradable material, comprising 45-89% by weight of polylactic acid, 10-50% of polybutylene succinate, and 1-5% of a binary graft copolymer; the binary graft copolymer is a product of a graft reaction of poly(dextral lactic acid) and poly(butylene succinate) on a main chain of an epoxy chain extender. Summary of the invention
[0006] In order to solve the shortcomings of PLA biodegradable materials, such as high hardness, large brittleness and poor heat resistance, in the first aspect, the present invention provides a polylactic acid composition, which comprises: polylactic acid; modified polybutylene succinate, and a nucleating agent; wherein the modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator; the functionalized modifier is selected from one or more of maleic anhydride (MA), glycidyl methacrylate (GMA), diglycidyl 4-cyclohexene-1,2-dicarboxylate, triglycidyl isocyanurate, vinyl triethoxysilane, and polypropylene carbonate;
[0007] The chain extender is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO), 1,3-phenylene-bis(2-oxazoline) (BOX-210), and hexamethylene diisocyanate (HDI);
[0008] The initiator is selected from one or more of tert-butyl perbenzoate (TBPB), di-tert-butyl peroxide (DTBP), benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), azobisisobutyronitrile (AIBN), hydroquinone (TPD), p-phenylenediamine (TDA), and pyroquinone (TPh);
[0009] The nucleating agent is selected from one or more of aryl phosphate salts, aryl dicarboxamides, oxalamide, 1,3,5-benzenetricarboxylic acid tris(neopentylamine), N,N',N"-tricyclohexyl-1,3,5-benzenetricarboxamide, cellulose, lignin, and inositol.
[0010] In one embodiment, the modified polybutylene succinate is prepared by a solid phase grafting reaction, which includes: reacting polybutylene succinate with a functionalized modifier in the presence of an initiator. In one embodiment, the solid phase grafting reaction is carried out under an inert gas environment, such as under a nitrogen environment. The solid phase grafting reaction can also be carried out in the presence of an auxiliary agent, such as reacting polybutylene succinate with a functionalized modifier in xylene in the presence of an initiator. The temperature at which the reaction is carried out in the solid phase grafting reaction can be about 60-120°C. In the solid phase grafting reaction, the amount of the functionalized modifier is 2-8% by weight of the polybutylene succinate, and the amount of the initiator is 0.1-1% by weight of the polybutylene succinate.
[0011] By generating a monomer of a graft chain on the polymer main chain, the compatibility of PLA and PBS is enhanced as a compatibilizer. The preparation method of polymer graft modified macromolecular material mainly includes solution method, melting method, radiation method and solid phase method etc. Among them, the temperature of solid phase graft reaction is low, the energy consumption is less, the occurrence of side reactions such as crosslinking and degradation is reduced, the grafting rate is high, the equipment and production process are relatively simple, and there is huge industrial development potential. In order to achieve the balance performance of toughness and heat resistance under the premise of controllable reaction, the present invention carries out a co-blending reaction of PLA and PBS modified by solid phase chemical grafting to realize the in-situ volume expansion of the interface. At the same time, a nucleating agent with self-assembly characteristics is introduced to improve the rapid crystallization nucleation of the blend, thereby obtaining higher heat resistance.
[0012] In a second aspect, the present invention also relates to a method for preparing a polylactic acid product, comprising the following steps: providing a polylactic acid composition according to the first aspect of the present invention, comprising:
[0013] Polylactic acid; modified polybutylene succinate, and a nucleating agent;
[0014] Wherein, the modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator;
[0015] The polylactic acid composition is melt-blended and then extruded to obtain in-situ toughened and modified polylactic acid;
[0016] The modified polylactic acid is subjected to isothermal crystallization treatment to obtain in-situ toughened heat-resistant modified polylactic acid;
[0017] The in-situ toughened heat-resistant modified polylactic acid is subjected to molding processing to obtain the polylactic acid product.
[0018] In one embodiment, melt blending comprises:
[0019] After the modified polybutylene succinate and polylactic acid are dried, a nucleating agent is added and stirred to obtain a mixture;
[0020] The mixture was melted at 160-220°C and mixed uniformly.
[0021] In a third aspect, the present invention also relates to use of the polylactic acid composition of the first aspect of the present invention in preparing food packaging materials.
[0022] In a fourth aspect, the present invention also relates to a polylactic acid product prepared by the method of the second aspect of the present invention.
[0023] In a fifth aspect, the present invention also relates to the use of the polylactic acid product of the fourth aspect of the present invention in food packaging materials such as cast film, blown film, biaxially stretched film and injection molded containers, preferably in coffee capsule packaging materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figures are scanning electron microscope morphology images of the products of Comparative Examples 2 and 3; wherein, (a) is a scanning electron microscope morphology image of the product of Comparative Example 2 at a scale of 100 μm; (a') is a scanning electron microscope morphology image of the product of Comparative Example 2 at a scale of 10 μm; (b) is a scanning electron microscope morphology image of the product of Comparative Example 3 at a scale of 100 μm; (b') is a scanning electron microscope morphology image of the product of Comparative Example 3 at a scale of 10 μm.
[0025] Figure 2 The figures are scanning electron microscope morphology images of the products of Examples 7 and 10; wherein, (a) is a scanning electron microscope morphology image of the product of Example 7 at a scale of 100 μm; (a') is a scanning electron microscope morphology image of the product of Example 7 at a scale of 10 μm; (b) is a scanning electron microscope morphology image of the product of Example 10 at a scale of 100 μm; (b') is a scanning electron microscope morphology image of the product of Example 10 at a scale of 10 μm.
[0026] Figure 3 The polarizing microscope morphology images of the products of the compositions of Example 12 and Comparative Example 1 after being subjected to isothermal crystallization treatment at 110°C for different periods of time; wherein, a) is a polarizing microscope morphology image of the product obtained by the composition of Comparative Example 1 without isothermal crystallization treatment at 110°C; (a') is a polarizing microscope morphology image of the product obtained by the composition of Comparative Example 1 after isothermal crystallization treatment at 110°C for 5 minutes; (b) is a polarizing microscope morphology image of the product obtained by the composition of Example 12 without isothermal crystallization treatment at 110°C; (b') is a polarizing microscope morphology image of the product obtained by isothermal crystallization treatment at 110°C for 0.5 minutes of the composition of Example 12. DETAILED DESCRIPTION
[0027] General Definitions and Terminology
[0028] Unless otherwise indicated, all publications, patent applications, patents, and other references mentioned herein are incorporated by reference in their entirety.
[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In the event of a conflict, the definitions provided herein shall prevail.
[0030] Unless otherwise indicated, all percentages, parts, ratios, etc. are by weight.
[0031] When quantity, concentration or other value or parameter is given as range, preferred range or preferred upper limit and lower limit or specific value, it should be understood as specifically disclosing all ranges formed by paired values from any upper limit range or preferred value and any lower limit range or preferred value, regardless of whether the range is disclosed separately. Unless otherwise stated, when numerical range is quoted herein, the range refers to including its endpoints and integers and fractions within all such ranges. The scope of the present invention is not limited to the specific numerical value quoted when defining the range. For example, "2-8" covers 2, 3, 4, 5, 6, 7, 8 and any sub-range consisting of any two values therein, such as 2-6, 3-5.
[0032] The terms "about" and "approximately" when used with a numerical variable generally refer to the value of that variable and all values of that variable are within experimental error (e.g., within a 95% confidence interval for the mean) or within ±10% of the specified value, or a wider range.
[0033] The terms "comprises", "includes", "has", "contains" or "involves" and other variations thereof herein are inclusive or open-ended and do not exclude other unlisted elements or method steps. It will be understood by those skilled in the art that the above terms such as "comprising" encompass the meaning of "consisting of". The expression "consisting of" excludes any element, step or ingredient not specified. The expression "consisting essentially of" means that the scope is limited to the specified elements, steps or ingredients, plus the optional presence of elements, steps or ingredients that do not substantially affect the basic and novel features of the claimed subject matter. It will be understood that the expression "comprising" encompasses the expressions "consisting essentially of" and "consisting of".
[0034] The term "selected from..." means that one or more elements in the group listed later are independently selected and may include combinations of two or more elements.
[0035] When values or end-points of a range are described herein, it should be understood that the disclosure includes the specific value or end-point cited.
[0036] As used herein, the terms "one or more" or "at least one" refer to one, two, three, four, five, six, seven, eight, nine or more.
[0037] In addition, if the number of parts or components of the present invention is not indicated before, it means that there is no limit to the number of occurrences (or existence) of the parts or components. Therefore, it should be interpreted as including one or at least one, and the singular form of the parts or components also includes the plural form, unless the numerical value obviously represents the singular.
[0038] As used herein, the term "optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and that the description includes both occurring and not occurring of said event or circumstance.
[0039] When describing methods, components or steps, the use of letters or numbers is only for the purpose of distinction, and does not limit these methods, components or steps to be performed in the order or sequence of the identification. Those skilled in the art can make reasonable adjustments.
[0040] When the lower and upper limits of a numerical range are disclosed, any numerical value and any included range falling within the range are specifically disclosed. In particular, each range of values disclosed herein (in the form of "about a to b", or equivalently, "approximately a to b", or equivalently, "about ab"), should be understood to represent each numerical value and range encompassed within the broader range.
[0041] The term "number average molecular weight" or number average molar mass as used herein can be determined by gel permeation chromatography (Viscotek TDA305) using polystyrene as a standard material. j The mole fraction of the molecule is X j , the number of molecules is N j , then the number average molecular weight for
[0042]
[0043] Unless otherwise specified, the molecular weight described herein is the number average molecular weight. The number average molecular weight and its distribution in the present invention can be measured, for example, using a gel permeation chromatography (GPC) instrument or a mass spectrometer.
[0044] In the present invention, "in-situ" reaction refers to a chemical process that directly reacts in the original reaction environment without transferring the reactants to another reaction environment. For example, in the polylactic acid composition of the present invention, during the melt blending process, polylactic acid and modified polybutylene succinate react in-situ without pre-treating the two for reaction.
[0045] In the present invention, "grafted polymer" may also be referred to as "grafted copolymer", which comprises a main chain and a branch chain connected to the main chain. For example, a grafted polymer having a main chain A and a branch chain B may be referred to as "A-grafted-B", "A grafted B", "AgB", "A-Graft-B", etc., and may also be referred to as "B grafted A". The main chain of the grafted polymer of the present invention is a long polymer chain, such as polybutylene succinate.
[0046] In the present invention, "chain extension polymer" may also be referred to as "chain extension copolymer", which is usually a chain extension copolymer in which the active groups in the chain extender react with the terminal active groups in the base polymer to further increase the molecular weight of the polymer, and includes a base polymer part and a chain extension part. For example, a chain extension polymer in which the base polymer is A and the chain extender is B may be referred to as "AB". In one embodiment, the base polymer of the present invention is polybutylene succinate.
[0047] In one aspect, the present invention provides a polylactic acid composition comprising:
[0048] Polylactic acid;
[0049] Modified polybutylene succinate, and
[0050] Nucleating agent;
[0051] in,
[0052] The modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator.
[0053] The functionalized modifier is selected from one or more of maleic anhydride (MA), glycidyl methacrylate (GMA), diglycidyl 4-cyclohexene-1,2-dicarboxylate, triglycidyl isocyanurate, vinyl triethoxysilane, and polypropylene carbonate;
[0054] The chain extender is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO), 1,3-phenylene-bis(2-oxazoline) (BOX-210), and hexamethylene diisocyanate (HDI);
[0055] The initiator is selected from one or more of tert-butyl perbenzoate (TBPB), di-tert-butyl peroxide (DTBP), benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), azobisisobutyronitrile (AIBN), hydroquinone (TPD), p-phenylenediamine (TDA), and pyroquinone (TPh);
[0056] The nucleating agent is selected from one or more of aryl phosphate salts, aryl dicarboxamides, oxalamide, 1,3,5-benzenetricarboxylic acid tris(neopentylamine), N,N',N"-tricyclohexyl-1,3,5-benzenetricarboxamide, cellulose, lignin, and inositol.
[0057] Polylactic acid (PLA)
[0058] Polylactic acid (PLA), also known as polylactide, is a polyester polymer formed by the polymerization of lactic acid monomers. It is a biodegradable material made from renewable plant resources. Polylactic acid has good mechanical and physical properties, including tensile strength, elongation at break and elastic modulus. Therefore, polylactic acid is widely used in food packaging, agriculture, medical and other fields. In the field of food packaging, polylactic acid can be used to make transparent, high-gloss food containers and films; in the agricultural field, it can be used to make agricultural geotextiles and mulch films; in the medical field, polylactic acid is used to produce disposable infusion sets and non-disassembly surgical sutures due to its good biocompatibility and bioabsorbability. Polylactic acid includes a mixture of any one or more of left-handed polylactic acid (PLLA), right-handed polylactic acid (PDLA) and meso-polylactic acid (PDLLA).
[0059] In one embodiment, in the polylactic acid composition of the present invention, the content of polylactic acid is about 50-90 parts by weight, for example, the content of polylactic acid is about 50 parts by weight, 51 parts by weight, 52 parts by weight, 53 parts by weight, 54 parts by weight, 55 parts by weight, 56 parts by weight, 57 parts by weight, 58 parts by weight, 59 parts by weight, 59.4 parts by weight, 60 parts by weight, 61 parts by weight, 62 parts by weight, 63 parts by weight, 64 parts by weight, 65 parts by weight, 66 parts by weight. In a preferred embodiment, the content of polylactic acid is about 59.4 parts by weight. In another preferred embodiment, the content of polylactic acid is about 79.2 parts by weight.
[0060] In one embodiment, the number average molecular weight of polylactic acid is in the range of about 6×10 4 -18×10 4 g / mol, preferably about 9×10 4 -15×10 4 g / mol. For example, the molecular weight of polylactic acid is 6×10 4 g / mol, 7×10 4 g / mol, 8×10 4 g / mol, 9×10 4 g / mol, 10×10 4 g / mol, 11×10 4 g / mol, 12×10 4 g / mol, 13×10 4g / mol, 14×10 4 g / mol, 15×10 4 g / mol, 16×10 4 g / mol, 17×10 4 g / mol, 18×10 4 g / mol, etc. The number average molecular weight described in the present invention is determined using a gel permeation chromatograph. The specific determination method is as follows: polylactic acid is dissolved in chloroform with a concentration of 0.25% by weight, and polystyrene is used as a standard material, and the number average molecular weight of the high melting point polylactic acid is obtained by gel permeation chromatography (instrument model: Viscotek TDA305). If the number average molecular weight is too high, the movement of the polylactic acid segment will be restricted, and the processing current may be overloaded during the material processing process, which is not conducive to subsequent blending; if the number average molecular weight is too low, the polylactic acid segment is easily decomposed at high temperature, so that the mechanical properties of the prepared product are poor.
[0061] Modified polybutylene succinate
[0062] Polybutylene succinate (PBS) is also a biodegradable aliphatic polyester with good thermal stability.
[0063] Modified polybutylene succinate includes modification by grafting reaction and modification by chain extension reaction. In the present invention, the modified polybutylene succinate generated by grafting reaction of polybutylene succinate is referred to as functionalized polybutylene succinate. For example, the modified polybutylene succinate prepared by reacting polybutylene succinate with a functionalized modifier in the presence of an initiator is functionalized polybutylene succinate.
[0064] In the present invention, functionalized polybutylene succinate is prepared by solid phase grafting reaction. Solid phase grafting is a heterogeneous chemical grafting method, which has significant advantages such as low reaction temperature, large versatility of reaction device, simple post-processing, etc. compared with traditional solution method and melting method. The solid phase grafting reaction includes: reacting polybutylene succinate with functionalized modifier in the presence of initiator. In the present invention, the solid phase grafting reaction is carried out under inert gas environment and normal pressure. Solid phase grafting can also be carried out in the presence of auxiliary agent, for example, reacting polybutylene succinate with functionalized modifier in xylene in the presence of initiator. In one embodiment, in an inert gas environment, in the presence of initiator, polymer material, functionalized modifier and other optional auxiliary agents are reacted, wherein the amount of functionalized modifier is 2-8% of the weight of polybutylene succinate, and the amount of initiator is 0.1-1% of the weight of polybutylene succinate. Those skilled in the art can select a suitable reaction temperature as required, for example, the reaction temperature is about 60-120° C. In a specific embodiment, the solid phase grafting reaction comprises: in an inert gas environment, in the presence of an initiator, the liquid nitrogen frozen and crushed polybutylene succinate powder and the functionalized modifier are subjected to a normal pressure blending reaction at a temperature of about 60-120° C., wherein the amount of the functionalized modifier is 2-8% of the weight of the polybutylene succinate, and the amount of the initiator is 0.1-1% of the weight of the polybutylene succinate. In a preferred embodiment, the temperature of the solid phase grafting reaction is about 60-100° C., for example, 60° C., 65° C., 70° C., 75° C., 80° C., 85° C., 90° C., 95° C., 100° C. In another preferred embodiment, the duration of the solid phase grafting reaction is about 10-20h, preferably about 12-16h, for example, about 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, etc. Those skilled in the art can adjust the amount of the auxiliary agent used in the solid phase grafting reaction of the present invention accordingly as needed. For example, when xylene is used as an auxiliary agent in the solid phase grafting reaction, the amount of xylene is about 5-15ml, for example, about 5ml, 6ml, 7ml, 8ml, 9ml, 10ml, 11ml, 12ml, 13ml, 14ml, 15ml.
[0065] In one embodiment, in the polylactic acid composition of the present invention, the content of modified polybutylene succinate is about 9.8-50 weight parts, for example, the content of modified polybutylene succinate is about 10 weight parts, 15 weight parts, 19 weight parts, 19.8 weight parts, 20 weight parts, 25 weight parts, 30 weight parts, 35 weight parts, 39 weight parts, 39.6 weight parts, 40 weight parts, 45 weight parts, 50 weight parts. In a preferred embodiment, the content of modified polybutylene succinate is about 19.8 weight parts. In another preferred embodiment, the content of modified polybutylene succinate is about 39.6 weight parts.
[0066] Functionalized modifiers
[0067] Functionalized modifier is a chemical substance used to change the properties or performance of a substance. It introduces specific functional groups through chemical reactions to adjust and optimize material properties. Its uses include improving the mechanical properties of materials, improving chemical stability, enhancing heat resistance and chemical corrosion resistance, etc. In the present invention, the functionalized modifier is selected from one or more of maleic anhydride (MA), glycidyl methacrylate (GMA), 4-cyclohexene-1,2-dicarboxylic acid diglycidyl ester, triglycidyl isocyanurate, vinyl triethoxysilane, polypropylene carbonate, preferably one or more of maleic anhydride (MA) and glycidyl methacrylate (GMA). In one embodiment, the functionalized modifier is maleic anhydride. In another embodiment, the functionalized modifier is glycidyl methacrylate.
[0068] In the present invention, the amount of functionalized modifier is about 2-8% of the weight of polybutylene succinate, preferably about 3-6%, for example about 2%, 2.5%, 3.0%, 3.1%, 3.2%, 3.5%, 4.0%, 4.1%, 4.2%, 4.5%, 5.0%, 5.2%, 5.3%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0% etc. In one embodiment, the amount of maleic anhydride is about 3.1%, 4.2% or 5.3% of the weight of polybutylene succinate. In another embodiment, the amount of glycidyl methacrylate is about 4.2% or 5.3% of the weight of polybutylene succinate.
[0069] Chain Extender
[0070] Chain extenders are chemical substances that react with functional groups on polymer chains to extend the molecular chain and increase the molecular weight. Chain extenders are usually used to improve the mechanical properties and process properties of materials.
[0071] In the present invention, the chain extender is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO), 1,3-phenylene-bis(2-oxazoline) (BOX-210), and hexamethylene diisocyanate (HDI), preferably 2,2'-(1,3-phenylene)bis(2-oxazoline). In one embodiment, the chain extender is 2,2'-(1,3-phenylene)bis(2-oxazoline).
[0072] In the present invention, the amount of chain extender is about 2-8% by weight of polybutylene succinate, preferably about 3-6%, such as about 2%, 2.5%, 3.0%, 3.1%, 3.2%, 3.5%, 4.0%, 4.1%, 4.2%, 4.5%, 5.0%, 5.2%, 5.3%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, etc. In one embodiment, the amount of 2,2'-(1,3-phenylene)bis(2-oxazoline) is about 3.1% or 4.2% by weight of polybutylene succinate.
[0073] Initiator
[0074] An initiator is a substance that can react with double bonds or epoxy groups in polymer molecules to form new chemical bonds, promote cross-linking reactions, and thus help modify polymers. Common initiators include peroxides, azos, organic peroxides, and other types.
[0075] In the present invention, the initiator is selected from one or more of tert-butyl perbenzoate (TBPB), di-tert-butyl peroxide (DTBP), benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), azobisisobutyronitrile (AIBN), hydroquinone (TPD), p-phenylenediamine (TDA), hydroquinone (TPh), preferably one or more of benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP). In one embodiment, the initiator is benzoyl peroxide. In another embodiment, the initiator is diisopropyl peroxide. In yet another embodiment, the initiator is diisopropyl peroxydicarbonate. In a specific embodiment, the initiator is a combination of benzoyl peroxide and diisopropyl peroxide. In the present invention, the weight ratio of benzoyl peroxide to dicumyl peroxide can be about 1:2-2:1, preferably about 1:1. In another specific embodiment, the initiator is a combination of benzoyl peroxide and diisopropyl peroxydicarbonate. In the present invention, the weight ratio of benzoyl peroxide to diisopropyl peroxydicarbonate can be about 1:2-2:1, preferably about 1:1.
[0076] In one embodiment, the initiator is used in an amount of about 0.1-1% by weight of the polybutylene succinate, preferably about 0.2-0.5%, for example 0.1%, 0.2%, 0.30%, 0.31%, 0.32%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc.
[0077] In the present invention, the modified polybutylene succinate is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline)-extended polybutylene succinate (PBS-PBO), glycidyl methacrylate-grafted polybutylene succinate (PBS-g-GMA), and maleic anhydride-grafted polybutylene succinate (PBS-g-MA).
[0078] PBS-PBO refers to the product obtained by chain extension reaction modification of polybutylene succinate (PBS) and 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO). In one embodiment, the number average molecular weight of PBS-PBO is about 8×10 4 -18×10 4 g / mol, preferably about 9.5×10 4 -15×10 4 g / mol, for example, about 8×10 4 g / mol, 9×10 4 g / mol, 9.5810×10 4 g / mol, 9.7270×10 4 g / mol, 10×10 4 g / mol, 11×10 4 g / mol, 12×10 4 g / mol, 13×10 4 g / mol, 14×10 4 g / mol, 15×10 4 g / mol, 16×10 4 g / mol, 17×10 4 g / mol, 18×10 4g / mol. In another embodiment, the molecular weight distribution of PBS-PBO is about 1.3-2.2, preferably about 1.5-2.0, such as about 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2. In yet another embodiment, the melt index of PBS-PBO is about 4-8 g / 10 min, preferably about 5.5-6.5 g / 10 min, such as about 4 g / 10 min, 4.5 g / 10 min, 5 g / 10 min, 5.5 g / 10 min, 5.6 g / 10 min, 5.8 g / 10 min, 6.0 g / 10 min, 6.2 g / 10 min, 6.5 g / 10 min, 7 g / 10 min, 7.5 g / 10 min, 8 g / 10 min, etc.
[0079] PBS-g-GMA refers to the product obtained by grafting polybutylene succinate (PBS) with glycidyl methacrylate (GMA). Those skilled in the art know that, depending on the conditions of the grafting reaction, glycidyl methacrylate can react at appropriate carbon atom positions in polybutylene succinate. In one embodiment, the number average molecular weight of PBS-g-GMA is about 7×10 4 -15×10 4 g / mol, preferably about 9×10 4 -13×10 4 g / mol, for example, about 7×10 4 g / mol, 8×10 4 g / mol, 9×10 4 g / mol, 9.120×10 4 g / mol, 9.1180×10 4 g / mol, 10×10 4 g / mol, 10.1200×10 4 g / mol, 11×10 4 g / mol, 11.9070×10 4 g / mol, 12×10 4 g / mol, 13×10 4 g / mol, 14×10 4 g / mol, 15×10 4In another embodiment, the molecular weight distribution of PBS-g-GMA is about 1.4-2.3, preferably about 1.6-2.1, such as 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3. In another embodiment, the melt index of PBS-g-GMA is about 4-9 g / 10min, preferably about 5.0-7.5 g / 10min, for example, about 4 g / 10min, 4.5 g / 10min, 5 g / 10min, 5.3 g / 10min, 5.4 g / 10min, 5.5 g / 10min, 6.0 g / 10min, 6.5 g / 10min, 7 g / 10min, 7.2 g / 10min, 7.4 g / 10min, 7.5 g / 10min, 8 g / 10min, 8.5 g / 10min, 9.0 g / 10min, etc.
[0080] PBS-g-MA refers to the product obtained by grafting polybutylene succinate (PBS) with maleic anhydride (MA). Those skilled in the art know that, depending on the conditions of the grafting reaction, maleic anhydride can react at appropriate carbon atom positions in polybutylene succinate. In one embodiment, the number average molecular weight of PBS-g-MA is about 8×10 4 -16×10 4 g / mol, preferably about 9×10 4 -13×10 4 g / mol, for example, about 8×10 4 g / mol, 9×10 4 g / mol, 9.2580×10 4 g / mol, 10×10 4 g / mol, 10.6870×10 4 g / mol, 10.8870×10 4 g / mol, 10.8930×10 4 g / mol, 11×10 4 g / mol, 11.1170×10 4 g / mol, 12×10 4 g / mol, 12.0240×10 4 g / mol, 13×10 4 g / mol, 14×10 4 g / mol, 15×10 4 g / mol, 16×10 4 g / mol, 17×10 4 g / mol, 18×10 4In another embodiment, the molecular weight distribution of PBS-g-MA is about 1.3-2.2, preferably about 1.5-2.0, such as about 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2. In another embodiment, the melt index of PBS-g-MA is about 4-9 g / 10min, preferably about 5.0-7.0 g / 10min, for example, about 4 g / 10min, 4.5 g / 10min, 5 g / 10min, 5.1 g / 10min, 5.2 g / 10min, 5.5 g / 10min, 5.7 g / 10min, 5.8 g / 10min, 6.0 g / 10min, 6.2 g / 10min, 6.5 g / 10min, 7 g / 10min, 7.1 g / 10min, 7.4 g / 10min, 7.5 g / 10min, 8 g / 10min, 8.5 g / 10min, 9.0 g / 10min, etc.
[0081] In one embodiment, the number average molecular weight of the modified polybutylene succinate is in the range of about 6×10 4 g / mol-18×10 4 g / mol, preferably 9×10 4 -15×10 4 g / mol, for example 6×10 4 g / mol, 7×10 4 g / mol, 8×10 4 g / mol, 9×10 4 g / mol, 9.0120×10 4 g / mol, 9.1180×10 4 g / mol, 9.2580×10 4 g / mol, 9.5810×10 4 g / mol, 9.7270×10 4 g / mol, 10×10 4 g / mol, 10.1200×10 4 g / mol, 10.6870×10 4 g / mol, 10.8870×10 4 g / mol, 10.8930×10 4 g / mol, 11×10 4 g / mol, 11.1170×10 4 g / mol, 11.9070×10 4 g / mol, 12×10 4 g / mol, 12.0240×10 4 g / mol, 13×104 g / mol, 14×10 4 g / mol, 15×10 4 g / mol, etc.
[0082] Inorganic fillers
[0083] Inorganic fillers refer to powder materials with certain chemical composition, geometric shape and surface characteristics formed by processing inorganic minerals or non-metallic minerals. The role of inorganic fillers in the composition mainly includes improving the performance of composite materials, reducing costs and giving materials specific functions. They can be added to the matrix material as additives and play a role by occupying volume, thereby limiting the movement of polymer molecular chains and improving the physical properties of the material such as hardness, stiffness, and impact strength. At the same time, inorganic fillers can also improve the thermal properties, optical properties, electrical properties, and magnetic properties of the material. Inorganic fillers are widely used in polymer material industries such as plastics, rubber, and adhesives, as well as in the field of composite materials based on their chemical composition, particle size and distribution, particle shape, and surface properties.
[0084] The polylactic acid composition of the present invention optionally includes an inorganic filler. In one embodiment, the polylactic acid composition of the present invention comprises an inorganic filler. The inorganic filler can include calcium carbonate, talc, wollastonite, kaolin, mica, diatomaceous earth, carbon black, silicon dioxide, titanium oxide, barium sulfate, calcium sulfate, aluminum hydroxide, magnesium hydroxide and asbestos etc. In a preferred embodiment, the inorganic filler is selected from one or more of talc, wollastonite, calcium carbonate, calcium sulfate and kaolin.
[0085] In the present invention, polybutylene succinate is subjected to a specific modification treatment, and the obtained modified polybutylene succinate is further melt-blended with polylactic acid, a nucleating agent and an optional inorganic filler before extrusion, which can effectively improve the brittleness of polylactic acid and enhance its impact resistance.
[0086] Compared with the composition of polybutylene succinate, polylactic acid and a nucleating agent, the modified polybutylene succinate obtained by modifying polybutylene succinate using a combination of a specific functionalized modifier or a chain extender and an initiator can be used in the composition of the present invention to significantly improve the elongation at break and the notched impact strength of the polylactic acid product of the present invention, and significantly improve the flexibility, elasticity and impact resistance of the polylactic acid product of the present invention. In addition, by combining the modified polybutylene succinate with polylactic acid and a nucleating agent, the crystallinity of the polylactic acid therein can be significantly improved, thereby further improving the heat resistance of the polylactic acid product of the present invention.
[0087] Nucleating Agent
[0088] Nucleating agent is an additive used to improve the crystallization process of polymers. It accelerates the orderly arrangement of polymer molecular chains by providing additional crystal nuclei to form a smaller and more uniform crystal structure.
[0089] The nucleating agent used in the present invention has self-assembly capability, which refers to the ability of the nucleating agent to spontaneously organize and arrange itself under certain conditions to form an ordered structure.
[0090] In the present invention, the nucleating agent is selected from one or more of aryl phosphate salts, aryl dicarboxamides, oxalamide, 1,3,5-benzenetricarboxylic acid tris(neopentylamine), N,N′,N″-tricyclohexyl-1,3,5-benzenetricarboxamide, cellulose, lignin, and inositol, preferably one or more of aryl phosphate salts, aryl dicarboxamides, and oxalamides. In a preferred embodiment, the nucleating agent is an aryl phosphate salt. In another preferred embodiment, the nucleating agent is an aryl dicarboxamide. In yet another preferred embodiment, the nucleating agent is oxalamide.
[0091] In one embodiment, in the polylactic acid composition of the present invention, the content of the nucleating agent is about 0.2-1.5 weight parts, for example, the content of the nucleating agent is about 0.2 weight parts, 0.3 weight parts, 0.4 weight parts, 0.5 weight parts, 0.6 weight parts, 0.7 weight parts, 0.8 weight parts, 0.9 weight parts, 0.95 weight parts, 0.96 weight parts, 0.97 weight parts, 0.98 weight parts, 0.99 weight parts, 1.0 weight parts, 1.1 weight parts, 1.2 weight parts, 1.3 weight parts, 1.4 weight parts, 1.5 weight parts. In a preferred embodiment, the content of the nucleating agent is about 0.99 weight parts.
[0092] In one embodiment, the total weight of the polylactic acid, the modified polybutylene succinate and the nucleating agent is 100 parts by weight.
[0093] In the present invention, the nucleating agent is combined with polylactic acid, modified polybutylene succinate and an optional inorganic filler to accelerate the crystallization rate of polylactic acid, thereby improving the heat resistance and impact resistance of the composite product.
[0094] The polylactic acid composition of the present invention has high compatibility among the components of the composition by rationally combining polylactic acid, modified polybutylene succinate, a nucleating agent and an optional inorganic filler, and has excellent flexibility, heat resistance and impact resistance. At the same time, the composition also has good biodegradability, is friendly to the human body and the environment, and can be widely used in the preparation of various materials.
[0095] Uses of polylactic acid compositions
[0096] On the other hand, the present invention also relates to the use of the polylactic acid composition of the present invention for preparing food packaging materials. The polylactic acid composition of the present invention has good flexibility, excellent heat resistance and impact resistance, and can be applied to a variety of processing forms to obtain environmentally friendly and human health-friendly degradable products, especially for packaging materials with high requirements for storage time and storage effect. The food packaging materials prepared by the polylactic acid composition of the present invention include but are not limited to cast film, blown film, double-drawn film or injection molding container. In a preferred embodiment, the polylactic acid composition of the present invention is used to prepare coffee capsule packaging materials.
[0097] Polylactic acid product and preparation method thereof
[0098] In another aspect, the present invention relates to a method for preparing a polylactic acid product, which comprises the following steps: providing a polylactic acid composition of the present invention, comprising: polylactic acid; modified polybutylene succinate, and a nucleating agent; wherein the modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator; extruding the polylactic acid composition after melt blending to obtain an in-situ toughened modified polylactic acid; isothermally crystallizing the modified polylactic acid to obtain an in-situ toughened heat-resistant modified polylactic acid; molding the in-situ toughened heat-resistant modified polylactic acid to obtain the polylactic acid product. In the present invention, the functionalized modifier is selected from one or more of maleic anhydride (MA), glycidyl methacrylate (GMA), diglycidyl 4-cyclohexene-1,2-dicarboxylate, triglycidyl isocyanurate, vinyl triethoxysilane, and polypropylene carbonate. The chain extender is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO), 1,3-phenylene-bis(2-oxazoline) (BOX-210), and hexamethylene diisocyanate (HDI). The initiator is selected from one or more of tert-butyl perbenzoate (TBPB), di-tert-butyl peroxide (DTBP), benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), azobisisobutyronitrile (AIBN), hydroquinone (TPD), p-phenylenediamine (TDA), and hydroquinone (TPh). The nucleating agent is selected from one or more of aryl phosphate salts, aryl dicarboxamides, oxalamide, 1,3,5-benzenetricarboxylic acid tris(neopentylamine), N,N',N"-tricyclohexyl-1,3,5-benzenetricarboxamide, cellulose, lignin, and inositol.
[0099] Melt Blending
[0100] The polylactic acid composition of the present invention is melt blended, comprising: drying the modified polybutylene succinate and polylactic acid, adding a nucleating agent, stirring and mixing, and obtaining a mixture; and melt blending the mixture. A person skilled in the art may select a suitable drying method, such as vacuum drying, as needed. In the present invention, the drying temperature is about 70-90°C, such as about 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, etc. In the present invention, the drying time is about 2-10h, such as about 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, etc. A person skilled in the art may select a suitable melt blending temperature as needed. In one embodiment, the temperature of melt blending is about 160-220°C, for example, about 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, etc. In one embodiment, melt blending of the polylactic acid composition of the present invention comprises: vacuum drying the modified polybutylene succinate and polylactic acid at 80°C for 2-10h, adding a nucleating agent, stirring and mixing, to obtain a mixture; melting the mixture at 160-220°C and uniformly mixing.
[0101] In one embodiment, melt blending includes: vacuum drying the modified polybutylene succinate and polylactic acid at 80° C. for 4 hours, then adding a nucleating agent, stirring and mixing, to obtain a mixture. In another embodiment, melt blending includes: vacuum drying the modified polybutylene succinate and polylactic acid at 80° C. for 8 hours, then adding a nucleating agent, stirring and mixing, to obtain a mixture.
[0102] Extrusion, stretching, pelletizing
[0103] In the present invention, the polylactic acid composition of the present invention is melt blended and then extruded, and the extrudate may further include post-processing, such as stretching, pelletizing, etc. In the present invention, melt blending, extrusion, stretching, pelletizing, etc. can be performed using conventional equipment in the art, such as: a single-screw extruder, a twin-screw extruder. In the present invention, the melt after melt blending is extruded by a twin-screw extruder. In the present invention, the twin-screw extruder is set to control the temperature of more than 6 sections from the feed section to the head screw temperature, such as 6 sections, 7 sections, 8 sections, 9 sections, and 10 sections. In one embodiment, the twin-screw extruder is set to control the temperature of 8 sections from the feed section to the head screw temperature. In one embodiment, the temperature setting of each temperature zone of the twin-screw extruder is about 160-220° C., preferably about 180-200° C., for example, about 160° C., 165° C., 170° C., 175° C., 180° C., 185° C., 190° C., 195° C., 200° C., 205° C., 210° C., 215° C., 220° C., etc. In another embodiment, the screw aspect ratio of the twin-screw extruder is about 40:1 or more, preferably about 48:1 or more, for example, about 40:1 or more, 45:1 or more, 48:1 or more, 50:1 or more, etc. In another embodiment, the rotation speed of the twin-screw extruder is about 40-450rpm, preferably about 50-400rpm, for example, about 40rpm, 50rpm, 60rpm, 80rpm, 100rpm, 120rpm, 150rpm, 180rpm, 200rpm, 230rpm, 260rpm, 290rpm, 300rpm, 330rpm, 350rpm, 380rpm, 400rpm, etc.
[0104] When the polylactic acid composition of the present invention is melt-blended, the active groups in the modified polybutylene succinate can generate graft copolymers with polylactic acid in situ during the melt-blending step, and in-situ toughened modified polylactic acid is obtained by extrusion without the need to prepare a reinforcing phase in advance and then perform toughening by reaction, thereby simplifying the reaction steps. This enhances the compatibility of polybutylene succinate and polylactic acid, thereby improving the flexibility, heat resistance and impact resistance of the polylactic acid product prepared therefrom.
[0105] Isothermal crystallization
[0106] In the present invention, isothermal crystallization treatment refers to a crystallization process carried out at a constant temperature. Isothermal crystallization treatment needs to be carried out in a suitable temperature range. Too high a temperature causes the crystal to become a molten state and is not conducive to the crystallization process. In one embodiment, the temperature of isothermal crystallization treatment is about 90-150°C, preferably 110-150°C, for example, about 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. In a specific embodiment, the temperature of isothermal crystallization treatment is 110°C. In another embodiment, the time of isothermal crystallization treatment lasts about 0.5-5min, preferably about 1-2min, for example, about 0.5min, 1min, 1.2min, 1.4min, 1.6min, 1.8min, 2min, 2.5min, 3.0min, 3.5min, 4.0min, 4.5min, 5min, etc.
[0107] Through isothermal crystallization treatment, the crystallinity of the polylactic acid in the composition is improved, which can promote secondary crystallization, improve the stability and heat resistance of the polylactic acid composition, obtain in-situ toughened and heat-resistant modified polylactic acid, and help optimize the processing performance of the polylactic acid composition, enhance its physical and mechanical properties, and improve its tensile strength and toughness.
[0108] Forming
[0109] The particles can be processed into desired product forms, such as films (e.g., cast films, biaxial films, etc.), containers (e.g., injection molding containers), etc. The methods of the molding process include, but are not limited to, injection molding. Injection molding can be completed by a high-speed injection molding machine. The suitable content, molecular weight, and melt index range of each component in the polylactic acid composition of the present invention can make it have a processing property suitable for injection molding, and can obtain a polylactic acid product with excellent performance.
[0110] The preparation method of the polylactic acid product of the present invention can achieve the in-situ toughening effect of polylactic acid without the need to prepare the reinforcing phase in advance and then perform the toughening reaction, thereby simplifying the reaction steps. This makes the components more compatible and have higher bonding strength, thus having better thermodynamic stability, and the preparation process is simple, which is conducive to commercial production.
[0111] Polylactic acid products
[0112] In another aspect, the present invention also relates to a polylactic acid product, which is prepared by the method of the present invention.
[0113] The polylactic acid product of the present invention has excellent heat resistance and impact resistance, and is evaluated by parameters such as Vicat softening point, melt index, tensile strength, elongation at break, notched impact strength, and the like.
[0114] Vicat softening point
[0115] In the present invention, Vicat softening point refers to the softening point of a sample under a certain load and constant temperature rise conditions. 2 The temperature when the pressure needle is pressed into a depth of 1mm reflects the deformation characteristics of the material under heat and load.
[0116] The Vicat softening point of the polylactic acid product can be measured using conventional methods in the art, such as using GB / T1633-2000. In one embodiment, the Vicat softening point of the polylactic acid product of the present invention is measured by a Vicat softening temperature tester. The higher the Vicat softening temperature, the smaller the thermal deformation of the material when heated, and the better its heat resistance. The Vicat softening point of the polylactic acid product of the present invention is in the range of about 80-120°C, preferably about 90-110°C, for example, about 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 97°C, 97.9°C, 98°C, 98.3°C, 98.6°C, 98.6°C, 99°C, 99.5°C, 100°C, 100.4°C, 100.7°C, 102°C, 102.1°C, 102.9°C, 103.5°C, 104°C, 104.4°C, 106°C, 108°C, 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, etc.
[0117] Compared with the polylactic acid product made from the composition comprising polylactic acid and polybutylene succinate, the product made from the polylactic acid composition of the present invention comprising modified polybutylene succinate has a significantly improved Vicat softening point, which indicates that the polylactic acid product of the present invention has higher hardness, compressive strength and excellent heat resistance.
[0118] Melt index
[0119] In the present invention, the melt index refers to the outflow of a thermoplastic material through a standard die within a specified time under certain temperature and pressure conditions, expressed in grams per 10 minutes (g / 10min). This index reflects the melt flow properties of the material, that is, the ease with which the material becomes a fluid in a molten state.
[0120] The polylactic acid product of the present invention has a suitable melt index, which varies within a certain range according to the content of each component in the composition. The melt index of the polylactic acid product can be measured using conventional methods in the art, such as using GB / T 3682-2000. In one embodiment, the melt index of the polylactic acid product of the present invention is measured by a melt index meter (MFI-1211). The polylactic acid product of the present invention has a suitable melt index range and can be applied to various processing and molding processes, particularly cast extrusion and injection molding processes. The melt index range of the polylactic acid product of the present invention is about 5.0-8.2 g / 10min, for example, about 5.0 g / 10min, 5.5 g / 10min, 5.6 g / 10min, 5.8 g / 10min, 5.9 g / 10min, 6.0 g / 10min, 6.1 g / 10min, 6.4 g / 10min, 7.3 g / 10min, 7.4 g / 10min, 7.6 g / 10min, 7.7 g / 10min, 7.9 g / 10min, 8.0 g / 10min, and 8.1 g / 10min.
[0121] In the polylactic acid product made from the composition comprising polylactic acid and polybutylene succinate, the melt index increases with the increase of the content of polybutylene succinate. On the contrary, in the polylactic acid product of the present invention, the melt index decreases with the increase of the content of modified polybutylene succinate. When the content of polylactic acid in the composition is the same, the melt index of the product made from the polylactic acid composition of the present invention comprising modified polybutylene succinate is less than the melt index of the product made from the polylactic acid composition comprising polybutylene succinate, which shows that the polylactic acid product of the present invention has higher strength and higher toughness.
[0122] Tensile strength and elongation at break
[0123] In the present invention, tensile strength refers to the maximum stress that a material withstands when subjected to tension until it breaks. In the present invention, elongation at break refers to the ratio of the displacement value at break to the original length when a material is subjected to tension until it breaks.
[0124] The tensile strength and elongation at break of the polylactic acid product can be measured in a conventional manner in the art, for example, using GB / T 1043.1-2008 for determination. In one embodiment, the tensile strength and elongation at break of the polylactic acid product of the present invention are measured by a universal testing machine. The tensile strength of the polylactic acid product of the present invention is about 30-60MPa, preferably 40-50Mpa, for example, about 30MPa, 35MPa, 40MPa, 40.4MPa, 41.3MPa, 42.1MPa, 43.5MPa, 43.6MPa, 43.7MPa, 44.3MPa, 44.5MPa, 45.2MPa, 45.9MPa, 50MPa, 55MPa, 60MPa, etc. The elongation at break of the polylactic acid product of the present invention is about 80%-260%, preferably 85%-250%, for example, about 80%, 85%, 88%, 89.4%, 90%, 95%, 100%, 102.9%, 105%, 110%, 110.4%, 111.5%, 115%, 118.1%, 118.4%, 119.3%, 120.7%, 121.9%, 122.8%, 123.7%, 124.9%, 125.1%, 126.3%, 127.7%, 128.8%, 129.9%, 130.9%, 131.1%, 132.1%, 133.1%, 134.1%, 136.1%, 137.1%, 138.1%, 139.2%, 140.3%, 141.4%, 142.5%, 143.6%, 144.7%, 145.8%, 146.9%, 147.1%, 148. 20%, 125%, 129.2%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200%, 210%, 213.9%, 215%, 220%, 225%, 226.3%, 230%, 233.1%, 235%, 240%, 245%, 248.2%, 250%, etc.
[0125] Compared with the products made from the composition comprising polylactic acid and polybutylene succinate, the products made from the polylactic acid composition of the present invention comprising modified polybutylene succinate have significantly improved elongation at break, which indicates that the polylactic acid products of the present invention can be deformed to a greater extent before breaking, thereby making the material have better resistance to impact damage.
[0126] Notched impact strength
[0127] In the present invention, notched impact strength refers to the destructive strength of a material under an impact load when there is a notch in the material. This parameter reflects the material's ability to resist damage when facing a sudden impact and is an important indicator for measuring the toughness and impact resistance of the material. In actual engineering applications, many materials will have notches or cracks due to defects in the manufacturing process or damage during use, and these defects will significantly affect the mechanical properties and service life of the material. Therefore, understanding and evaluating the notched impact strength of a material is crucial to ensuring structural safety.
[0128] The notched impact strength of the polylactic acid product can be measured using conventional methods in the art, such as using GB / T1843-2008. In one embodiment, the notched impact strength of the polylactic acid product of the present invention is measured by an Izod impact tester. The notched impact strength of the polylactic acid product of the present invention is about 3.2-7 kJ·m -2 , preferably 3.5-6.5 kJ·m -2 , for example, about 3.2 kJ·m -2 、3.5kJ·m -2 、3.8kJ·m -2 、3.98kJ·m -2 , 4.0 kJ·m -2 4.12 kJ·m -2 4.13 kJ·m -2 4.2 kJ·m -2 4.22 kJ·m -2 4.24 kJ·m -2 , 4.3 kJ·m -2 4.33 kJ·m -2 4.39 kJ·m -2 4.4 kJ·m -2 4.42 kJ·m -2 , 4.5 kJ·m -2 4.6 kJ·m -2 4.8 kJ·m -2 , 5kJ·m -2 , 5.2 kJ·m -2 , 5.4 kJ·m -2 , 5.6 kJ·m -2 , 5.8 kJ·m -2 , 5.89 kJ·m -2 , 6kJ·m -2 、6.01kJ·m -2 、6.18kJ·m -2 、6.2kJ·m -2 、6.31kJ·m -2 、6.5kJ·m -2 wait.
[0129] Compared with the products made from the composition comprising polylactic acid and polybutylene succinate, the products made from the polylactic acid composition of the present invention comprising modified polybutylene succinate have significantly improved notched impact strength, which indicates that the polylactic acid products of the present invention are less likely to break or damage when subjected to impact loads and have higher durability and safety.
[0130] Crystallinity
[0131] Each component in the polylactic acid product prepared by the method of the present invention has a suitable crystallinity. Crystallinity refers to the proportion of the crystalline part in the internal structure of the material in the crystalline state. It is a quantitative indicator describing the crystalline state of the material and reflects the order of the arrangement of atoms, molecules or atomic groups in the crystal.
[0132] The crystallinity of polylactic acid products can be measured in a conventional manner in this area, for example, using differential scanning calorimetry (DSC) to measure. In one embodiment, in polylactic acid products of the present invention, the crystallinity of modified polybutylene succinate is about 8-20%, preferably about 10-17%, for example about 8%, 9%, 10%, 11.2%, 11.3%, 11.8%, 12%, 12.1%, 12.4%, 12.5%, 12.8%, 13%, 14%, 15%, 15.7%, 15.8%, 16%, 16.2%, 16.4%, 17%, 18%, 19%, 20% etc. In another embodiment, in the polylactic acid product of the present invention, the crystallinity of the polylactic acid is about 20-40%, preferably about 24-32%, for example, about 20%, 21%, 22%, 23%, 24%, 24.1%, 25%, 25.1%, 25.7%, 25.9%, 26%, 26.2%, 26.9%, 27%, 27.2%, 28%, 28.1%, 28.2%, 29%, 29.1%, 29.4%, 30%, 31%, 31.8%, 32, etc.
[0133] The composition of the present invention can improve the crystallinity and crystallization rate of polylactic acid in polylactic acid products. Therefore, the polylactic acid products of the present invention have the advantages of better toughness, higher strength and hardness, higher heat resistance, lower thermal expansion coefficient, higher transparency, lower air permeability and selective barrier to gas, shorter production cycle, reduced production energy consumption, higher weather resistance and chemical resistance. PLA with high crystallinity can effectively disperse external stress and reduce the generation and expansion of cracks due to the tighter and more orderly arrangement of molecular chains, thereby improving the toughness of the material; the crystal structure formed by rapid crystallization is more perfect, which helps to improve the tensile strength and compressive strength of PLA, making it less likely to deform or break when subjected to external forces. Fast crystallization speed means that PLA can form more crystals in a shorter time, and these crystals fill the inside of the material, increasing the hardness of the material and making it more wear-resistant and scratch-resistant. PLA with high crystallinity usually has a higher melting point, which means that when used in a high temperature environment, the material is not easy to soften or melt, and maintains good stability. The crystal structure formed by rapid crystallization can limit the movement of molecular chains, thereby reducing the thermal expansion coefficient of the material and reducing the dimensional changes caused by temperature changes. In PLA with high crystallinity, the crystal area accounts for a large proportion, and these areas have low permeability to gas molecules, thereby improving the gas barrier properties of the material. The crystal structure formed by rapid crystallization may have a certain selectivity and can block specific gas molecules, such as oxygen and carbon dioxide, which is particularly important in areas such as food packaging. PLA with a fast crystallization speed can quickly complete the crystallization process during processing, thereby shortening the entire processing cycle and improving production efficiency. Less heat is required during the rapid crystallization process, which helps to reduce energy consumption in the production process and achieve the goal of energy conservation and emission reduction. PLA with high crystallinity has strong resistance to environmental factors such as ultraviolet rays and humidity, and can maintain stable performance for a long time outdoors or in harsh environments. The crystal structure formed by rapid crystallization is more stable, can resist erosion by chemicals such as acids, alkalis, and salts, and extend the service life of the material.
[0134] Beneficial Effects
[0135] The invention relates to a polylactic acid composition, which comprises polylactic acid, modified polybutylene succinate and a nucleating agent. By rationally combining the components, the crystallization rate of the polylactic acid-based biodegradable material is improved, especially after a short-time annealing treatment, the polylactic acid product prepared from the polylactic acid composition of the invention has excellent heat resistance and improved impact resistance.
[0136] When the modified polybutylene succinate is prepared by a grafting reaction, the preparation method through a solid phase grafting reaction can be carried out at a lower temperature, reducing the occurrence of side reactions, and obtaining a modified polybutylene succinate with a high grafting rate. The active groups at the ends of the polybutylene succinate can generate a graft copolymer in situ with polylactic acid in the melt blending step, thereby enhancing the compatibility of polybutylene succinate and polylactic acid, thereby improving the flexibility, heat resistance and impact resistance of the polylactic acid products prepared therefrom.
[0137] The preparation method of the polylactic acid product of the present invention can achieve the in-situ toughening effect of polylactic acid without the need to prepare a reinforcing phase in advance, so that the components have stronger compatibility and higher bonding strength, thereby having better thermodynamic stability. The preparation process is simple and is conducive to commercial production.
[0138] The polylactic acid product of the present invention has excellent heat resistance and impact resistance, is biodegradable, is friendly to the human body and the environment, and can be widely used in materials in various fields, especially food packaging materials.
[0139] Example
[0140] The solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0141] It should be noted that the following examples are merely examples for clearly illustrating the technical solutions of the present invention, and are not intended to limit the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description, and it is not necessary and impossible to exhaustively list all the embodiments here, and the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention. Unless otherwise specified, the instruments, equipment, and reagents used herein are all commercially available.
[0142] Material
[0143] Polylactic acid (PLA): Zhejiang Hisun Biomaterials Co., Ltd., melting point is about 175.4°C, melt index is 8.3g / 10min, brand name is REVODE190.
[0144] Polybutylene succinate (PBS) was purchased from Zhuhai Jinfa Biomaterial Co., Ltd., with a melting point of 114.1°C, a melting index of 10g / 10min, and a brand name of A200MF NC801.
[0145] 2,2'-(1,3-phenylene)bis(2-oxazoline), maleic anhydride, and glycidyl methacrylate were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0146] Benzoyl peroxide (BPO), dicumyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), and oxalamide were purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.
[0147] Aryl phosphate salts were purchased from Shanxi Chemical Research Institute Co., Ltd.
[0148] Aryl dicarbonamide was purchased from Rika Co., Ltd.
[0149] Example 1
[0150] 1. Preparation of modified PBS resin: 9.7kg polybutylene succinate powder, 0.3kg 2,2'-(1,3-phenylene)bis(2-oxazoline), 0.03kg benzoyl peroxide and 10ml xylene were added into a reactor and heated for blending reaction. The reaction temperature was controlled to about 80°C and the reaction was carried out at normal pressure under nitrogen protection for 20h. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.6g / 10min (190°C, 2.16kg). The number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 95810g / mol.
[0151] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aromatic dicarbonamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0152] Example 2
[0153] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of glycidyl methacrylate, 0.03 kg of diisopropylbenzene peroxide and 10 ml of xylene were added to a reactor and heated for blending reaction. The reaction temperature was controlled to about 80 ° C, and the reaction was carried out at normal pressure under nitrogen protection for 20 hours. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.3 g / 10 min (190 ° C, 2.16 kg). The number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 101200 g / mol.
[0154] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aromatic dicarbonamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0155] Example 3
[0156] 1. Preparation of modified PBS resin: 9.7 kg of polybutylene succinate powder, 0.3 kg of maleic anhydride, 0.03 kg of diisopropyl peroxydicarbonate and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 80 ° C, and the reaction was carried out at normal pressure under nitrogen protection for 20 hours. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.1 g / 10 min (190 ° C, 2.16 kg). The number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 108870 g / mol.
[0157] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aromatic dicarbonamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0158] Example 4
[0159] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of 2,2'-(1,3-phenylene)bis(2-oxazoline), 0.03 kg of initiator (benzoyl peroxide: diisopropylbenzene peroxide = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction, and the reaction temperature was controlled to about 100° C., and the reaction was carried out at normal pressure under nitrogen protection for 12 hours. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 6.2 g / 10 min (190° C., 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 97270 g / mol.
[0160] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg oxalamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0161] Example 5
[0162] 1. Preparation of modified PBS resin: 9.5 kg of polybutylene succinate powder, 0.5 kg of glycidyl methacrylate, 0.03 kg of initiator (benzoyl peroxide: diisopropylbenzene peroxide = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 12 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 7.2 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 90120 g / mol.
[0163] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg oxalamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0164] Example 6
[0165] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of maleic anhydride, 0.03 kg of initiator (benzoyl peroxide: diisopropylbenzene peroxide = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 12 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.8 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 106870 g / mol.
[0166] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg oxalamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0167] Example 7
[0168] 1. Preparation of modified PBS resin: 9.5 kg of polybutylene succinate powder, 0.5 kg of glycidyl methacrylate, 0.03 kg of initiator (diisopropyl peroxide: diisopropyl peroxydicarbonate = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 90 ° C, and the reaction was carried out at normal pressure under nitrogen protection for 16 hours. The melt index (MFI) was tested by a melt index tester (MFI-1211) to be 7.4 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) to be 91180 g / mol.
[0169] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aryl phosphate salt was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0170] Example 8
[0171] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of maleic anhydride, 0.03 kg of initiator (dicumyl peroxide: diisopropyl peroxydicarbonate = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 90 ° C, and the reaction was carried out at normal pressure under nitrogen protection for 16 hours. The melt index (MFI) was tested by a melt index tester (MFI-1211) to be 7.1 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) to be 92580 g / mol.
[0172] 2. Preparation of PLA / modified PBS modified resin: 8kg PLA and 2kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aryl phosphate salt was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0173] Example 9
[0174] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of maleic anhydride, 0.03 kg of initiator (benzoyl peroxide: diisopropylbenzene peroxide = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 16 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.7 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 111170 g / mol.
[0175] 2. Preparation of PLA / modified PBS modified resin: 6kg PLA and 4kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aromatic dicarbonamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0176] Example 10
[0177] 1. Preparation of modified PBS resin: 9.5 kg of polybutylene succinate powder, 0.5 kg of glycidyl methacrylate, 0.03 kg of initiator (benzoyl peroxide: diisopropylbenzene peroxide = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 16 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.4 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 119070 g / mol.
[0178] 2. Preparation of PLA / modified PBS modified resin: 6kg PLA and 4kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg aromatic dicarbonamide was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0179] Embodiment 11
[0180] 1. Preparation of modified PBS resin: 9.6 kg of polybutylene succinate powder, 0.4 kg of maleic anhydride, 0.03 kg of initiator (diisopropyl peroxide: diisopropyl peroxydicarbonate = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 16 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 5.2 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA 305) and was 120240 g / mol.
[0181] 2. Preparation of PLA / modified PBS modified resin: 6kg PLA and 4kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg of aryl phosphate salt was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0182] Example 12
[0183] 1. Preparation of modified PBS resin: 9.5 kg of polybutylene succinate powder, 0.5 kg of maleic anhydride, 0.03 kg of initiator (diisopropyl peroxide: diisopropyl peroxydicarbonate = 1:1) and 10 ml of xylene were added to a reactor for heating and blending reaction. The reaction temperature was controlled to about 100 ° C, and the reaction was carried out at normal pressure for 16 hours under nitrogen protection. The melt index (MFI) was tested by a melt index tester (MFI-1211) and was 6.2 g / 10 min (190 ° C, 2.16 kg), and the number average molecular weight was measured by a gel permeation chromatograph (Viscotek TDA305) and was 108930 g / mol.
[0184] 2. Preparation of PLA / modified PBS modified resin: 6kg PLA and 4kg modified PBS resin were dehumidified and dried at 80℃ for 4h, then put into a mixer and mixed evenly, 0.1kg of aryl phosphate salt was added, and the mixture was mixed for 10min until evenly mixed, and then added into the hopper of a twin-screw extruder, and the temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and then mixed, extruded, pelletized, and dried. Then the temperature was set to about 110-150℃, and the duration was about 0.5-5min, and an isothermal crystallization treatment was performed to obtain in-situ toughened heat-resistant modified polylactic acid. The obtained in-situ toughened heat-resistant modified polylactic acid was molded by injection molding (SPEED-PACKⅡ of Zhenxiong Molding Machine) and the physical properties were tested.
[0185] Comparative Example 1
[0186] 10kg PLA resin was dehumidified and dried at 80℃ for 4h, and then added to the hopper of the twin-screw extruder. The temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and after blending, extrusion, pelletizing, and drying, it was formed by injection molding (SPEED-PACKⅡ of Chenxiong Plastic Machine) and physical property testing was performed.
[0187] Comparative Example 2
[0188] 8kg PLA and 2kg PBS resin were dehumidified and dried at 80℃ for 4h, then put into a blender to mix evenly, and then added into the hopper of a twin-screw extruder. The temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and after blending, extrusion, pelletizing, and drying, they were formed by injection molding (SPEED-PACKⅡ of Zhenxiong Plastics Machine) and physical property tests were performed.
[0189] Comparative Example 3
[0190] 6kg PLA and 4kg PBS resin were dehumidified and dried at 80℃ for 4h, then put into a blender to mix evenly, and then added into the hopper of a twin-screw extruder. The temperature of each temperature zone of the twin-screw extruder was set to about 180-195℃, and after blending, extrusion, pelletizing, and drying, they were formed by injection molding (SPEED-PACKⅡ of Chenxiong Plastics Machine) and physical property tests were performed.
[0191] test
[0192] The injection molded samples of the embodiments and comparative examples were tested according to the following test method. The results are shown in Table 1.
[0193] Melt index: measured using a melt index tester (MFI-1211) in accordance with GB / T 3682-2000 at 190°C and 2.16 kg.
[0194] Tensile strength and elongation at break: measured using a universal testing machine in accordance with GB / T 1043.1-2008 at a tensile rate of 50 mm / min.
[0195] Notched impact strength: measured using an Izod impact tester in accordance with GB / T 1843-2008 and tested at a pendulum energy of 2J.
[0196] Table 1
[0197]
[0198] The injection molded samples of the embodiments and comparative examples were tested according to the following test method. The results are shown in Table 2.
[0199] The crystallinity of the injection molded samples was tested by differential scanning calorimetry (TADSC25).
[0200] Vicat softening temperature: measured using a Vicat softening temperature tester (Jinjian JJ HDT / V series) in accordance with GB / T1633-2000, with a heating rate of 50°C / h and a pressure of 50N.
[0201] Table 2
[0202]
[0203]
[0204] According to the results in Table 1, the polylactic acid products of the embodiments of the present invention have good tensile strength. Compared with Comparative Examples 1-3, the polylactic acid products of the embodiments of the present invention have a smaller melt index, significantly improved elongation at break and notched impact strength. This shows that the injection molded products prepared from the polylactic acid composition of the embodiments of the present invention have higher strength, better toughness and more excellent impact resistance than the injection molded products prepared using polylactic acid alone and the injection molded products prepared using the composition of polylactic acid and polybutylene succinate, and thus have higher durability and safety.
[0205] According to the results of Example 8 and Example 11, the melt index of the polylactic acid product prepared by the polylactic acid composition of the embodiment of the present invention is inversely correlated with the content of the modified PBS therein, and the elongation at break and the notched impact strength are positively correlated with the content of the modified PBS therein. This shows that the strength, toughness and impact resistance of the polylactic acid product of the embodiment of the present invention are positively correlated with the content of the modified PBS in the polylactic acid composition of the present invention. The content of the modified PBS in the polylactic acid composition of the present invention increases, and the strength, toughness and impact resistance of the polylactic acid product of the embodiment of the present invention are enhanced.
[0206] It is worth noting that, according to the results of Comparative Examples 1-3, the melt index of the comparative polylactic acid product is positively correlated with the content of PBS in the comparative example. The higher the content of PBS in the comparative example, the greater the melt index of the product. However, according to Examples 1-12, the melt index of the polylactic acid product of the embodiment of the present invention is inversely correlated with the content of modified PBS in the polylactic acid composition of the present invention. The higher the content of modified PBS in the polylactic acid product of the embodiment of the present invention, the smaller the melt index of the product. This shows that the polylactic acid product of the present invention is quite different from the polylactic acid product in the comparative example, and the modified PBS has an important influence on the polylactic acid product of the present invention.
[0207] According to the results in Table 2, compared with Comparative Examples 1-3, the polylactic acid products of the embodiments of the present invention have significantly improved Vicat softening points, which indicates that the injection molded products prepared from the polylactic acid composition of the present invention have higher hardness, compressive strength and excellent heat resistance.
[0208] According to the results of Examples 1-8 and Comparative Example 2, when the polylactic acid content in the polylactic acid composition is equivalent, the polylactic acid crystallinity in the polylactic acid product of the present invention is significantly higher than that of the polylactic acid product of Comparative Example 2. The same conclusion can be drawn from Examples 9-12 and Comparative Example 3. This shows that the polylactic acid composition of the present invention can significantly increase the crystallization efficiency of polylactic acid, thereby improving the toughness, impact resistance and heat resistance of the product made therefrom.
[0209] In summary, the polylactic acid composition of the present invention solves the problems that polylactic acid and polybutylene succinate are difficult to be compatible, polylactic acid has poor toughness and slow crystallization rate by combining polylactic acid with modified polybutylene succinate and a nucleating agent, so that the polylactic acid products prepared therefrom have better heat resistance and impact resistance, and also have biodegradability, and are friendly to the environment and the human body. The composition of the present invention and its products can be widely used in the fields of food packaging, agriculture, medical treatment, etc., especially food packaging materials, and have good application prospects.
[0210] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A polylactic acid composition, comprising: Polylactic acid, Modified polybutylene succinate, and Nucleating agent; in, The modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator. The functionalized modifier is selected from one or more of maleic anhydride (MA), glycidyl methacrylate (GMA), diglycidyl 4-cyclohexene-1,2-dicarboxylate, triglycidyl isocyanurate, vinyl triethoxysilane, and polypropylene carbonate; The chain extender is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline) (PBO), 1,3-phenylene-bis(2-oxazoline) (BOX-210), and hexamethylene diisocyanate (HDI); The initiator is selected from one or more of tert-butyl perbenzoate (TBPB), di-tert-butyl peroxide (DTBP), benzoyl peroxide (BPO), diisopropyl peroxide (DCP), diisopropyl peroxydicarbonate (IPP), 2,3-dimethyl 2,3-diphenylbutane (DMDPB), azobisisobutyronitrile (AIBN), hydroquinone (TPD), p-phenylenediamine (TDA), and pyroquinone (TPh); The nucleating agent is selected from one or more of aryl phosphate salts, aryl dicarboxamides, oxalamide, 1,3,5-benzenetricarboxylic acid tris(neopentylamine), N,N',N"-tricyclohexyl-1,3,5-benzenetricarboxamide, cellulose, lignin, and inositol.
2. The polylactic acid composition according to claim 1, wherein The functionalized modifier is selected from one or more of maleic anhydride and glycidyl methacrylate; and / or The chain extender is 2,2'-(1,3-phenylene)bis(2-oxazoline); and / or The initiator is selected from one or more of benzoyl peroxide (BPO), dicumyl peroxide (DCP), and diisopropyl peroxydicarbonate (IPP); and / or The nucleating agent is selected from one or more of aryl phosphates, aryl dicarboxamides, and oxalamides.
3. The polylactic acid composition according to claim 1 or 2, wherein The content of the polylactic acid is 50-90 parts by weight, The content of the modified polybutylene succinate is 9.8-50 parts by weight, The content of the nucleating agent is 0.2-1.5 parts by weight.
4. The polylactic acid composition according to claim 1, wherein The number average molecular weight of the polylactic acid is in the range of 9×10 4 -15×10 4 g / mol; and / or The number average molecular weight of the modified polybutylene succinate is in the range of 6×10 4 -18×10 4 g / mol.
5. The polylactic acid composition according to claim 1, wherein The modified polybutylene succinate is selected from one or more of 2,2'-(1,3-phenylene)bis(2-oxazoline)-extended polybutylene succinate (PBS-PBO), glycidyl methacrylate-grafted polybutylene succinate (PBS-g-GMA), and maleic anhydride-grafted polybutylene succinate (PBS-g-MA).
6. The polylactic acid composition according to claim 5, wherein The number average molecular weight of the PBS-PBO is 8×10 4 -18×10 4 g / mol, with a molecular weight distribution of 1.5-2.0; and / or The number average molecular weight of the PBS-g-GMA is 7×10 4 -15×10 4 g / mol, with a molecular weight distribution of 1.6-2.1; and / or The number average molecular weight of the PBS-g-MA is 8×10 4 -16×10 4 g / mol, and the molecular weight distribution is 1.5-2.
0.
7. The polylactic acid composition according to claim 1, wherein The polylactic acid composition further comprises an inorganic filler; Preferably, The inorganic filler is selected from one or more of talc, wollastonite, calcium carbonate, calcium sulfate and kaolin.
8. A method for preparing a polylactic acid product, comprising the following steps: Provided is a polylactic acid composition according to any one of claims 1 to 7, comprising: Polylactic acid; modified polybutylene succinate, and a nucleating agent; Wherein, the modified polybutylene succinate is prepared by reacting polybutylene succinate with a functionalized modifier or a chain extender in the presence of an initiator; The polylactic acid composition is melt-blended and then extruded to obtain in-situ toughened and modified polylactic acid; The modified polylactic acid is subjected to isothermal crystallization treatment to obtain in-situ toughened heat-resistant modified polylactic acid; The in-situ toughened heat-resistant modified polylactic acid is subjected to molding processing to obtain the polylactic acid product.
9. The method of claim 8, wherein: The modified polybutylene succinate is prepared by solid phase grafting reaction.
10. The method of claim 9, wherein: The solid phase grafting reaction comprises: reacting polybutylene succinate with a functionalized modifier in the presence of an initiator; Preferably, The functionalized modifier is selected from one or more of maleic anhydride (MA) and glycidyl methacrylate (GMA); The initiator is selected from one or more of benzoyl peroxide (BPO), dicumyl peroxide (DCP), and diisopropyl peroxydicarbonate (IPP); The reaction is carried out at a temperature of 60-120°C; The amount of the functional modifier used is 2-8% by weight of the polybutylene succinate, and the amount of the initiator used is 0.1-1% by weight of the polybutylene succinate.
11. The method according to any one of claims 8 to 10, wherein The melt blending comprises: After drying the modified polybutylene succinate and the polylactic acid, adding the nucleating agent and stirring and mixing to obtain a mixture; The mixture is melted at 160-220° C. and uniformly mixed; in, The drying temperature is 70-90°C, and the drying time is 2-10h; and / or The extrusion is carried out by a twin-screw extruder, and the screw temperature is set to be controlled in more than 6 sections from the feed section to the head, the set temperature of each temperature zone is 160-220°C, the screw aspect ratio is more than 40:1, and the screw speed is 50-400rpm; and / or The isothermal crystallization treatment is performed at a temperature of 90-150° C. and lasts for 0.5-5 min; and / or The molding process is injection molding.
12. Use of the polylactic acid composition according to any one of claims 1 to 7 for preparing food packaging materials; Preferably, the food packaging material comprises a cast film, a blown film, a double-stretched film or an injection molded container; More preferably, the food packaging material is coffee capsule packaging material.
Citation Information
Patent Citations
Compatilizer suitable for modification processing of biodegradable material and preparation and application thereof
CN115558070A
Poly(butylene succinate) dihydric alcohol-based polyurethane prepolymer modified and toughened PLA material and application and preparation method thereof
CN109912949A
Degradable plastic composition as well as preparation method and application thereof
CN111995848A
Modified poly (propylene carbonate) PBS (Phosphate Buffer Solution) blending material and preparation method thereof
CN118006107A
Biodegradable Composition
US20210347985A1